Quality of life of the rural community: a comparison between three cities - Md. Yassin, Sulaiman; Mohamed Shaffril, Hayrol Azril; Abu Samah, Bahaman; Hassan, Md. Salleh; Othman, Mohd Shahwahid; Abu Samah, Asnarulkhadi; Ramli, Siti Aisyah (Science Publications, 2011)
Problem statement: Pahang and Muar Rivers are two major rivers in Malaysia. In the past, these two rivers did play an important role in flourishing the economic activities of the local community and upgrading their quality of life. Does the community along these two rivers have a good quality of life? Answers for this question will bring us to the main objective of this study which is to investigate the level of quality of life of the community living along Pahang River and Muar River and to investigate any difference that might occur between the communities in Pekan, Bahau and Muar. Approach: Each of the cities is represented by 300 respondents making the overall total respondents selected for this study was 900. This is a quantitative study and a questionnaire was used to gain the data needed. A total of seven aspects of quality of life namely home condition, physical environment, safety at the areas, social involvement and relationship, education, financial and job security and infrastructure facilities had been studied. Results: Results gained have revealed that community along Pahang River and Muar River do have a high level of quality of life. And further analysis using ANOVA have shown that there are significant differences in six of the aspects of quality of life studied. There was no significant difference identified in the aspect of education. Conclusion/Recommendation: It can be concluded that the community that live along Pahang River and Muar River have a high level in all aspects of QOL studied. It can be concluded that community in Pekan managed to record the highest mean score in three aspects of quality of life namely (1) physical environment; (2) safety at the areas and (3) social involvement and relationship. Community in Muar managed to record the highest mean score in three aspects namely (1) education; (2) financial and job security and 3) infrastructure facilities while community if Bahau was identified to have the highest mean score in the aspect of home condition.